Reaksi Pasar Atas Pengumuman Anugerah Program Penilaian Peringkat Kinerja Perusahaan dalam Pengelolaan Lingkungan Hidup - Wirajaya, I Gde Ary; Pangestu, Teresia Arta (E-Jurnal Akuntansi, 2021)
This study aims to examine the market's reaction to information regarding the announcement of a company performance rating assessment program award in environmental management. Market reaction is measured by abnormal return around the announcement date of the environmental management program. This research is conducted at the Indonesia Stock Exchange. The population in this study are all publicly listed companies receiving PROPER awards listed on the IDX in 2018 for a total of 51 companies. Samples that met the purposive sampling criteria are 50 companies. The analysis technique used is one sample t-test and independent samples t-test.  The results of this study indicate that there is a market reaction around the PROPER rating announcement date, and there is no different market reaction between companies with good ratings and companies with bad ratings. Keywords: Event Study; Abnormal Return; PROPER.